Pengaruh Regulasi Lingkungan dan Dekarbonisasi terhadap Strategi Ship-Recycling dalam Industri Pembuatan Kapal Global - Muhammad Rajab Buruto; Eliyanti A. Mokodompit (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The global maritime industry serves as the backbone of international trade. To address the impacts of climate change, the International Maritime Organization (IMO) has established ambitious targets, particularly through the IMO 2023 Strategy on the Reduction of GHG Emissions from Ships. The IMO holds the authority to issue regulations related to safety and marine pollution prevention, with the overarching goal of achieving net-zero emissions by or around 2050. Shipbuilding is a multi-stage manufacturing process that integrates various specialized resources, involves complex functions, and requires a high level of construction quality to ensure both safety and operational performance. The dismantling process of decommissioned vessels is referred to as ship recycling. This study employs a literature review (library research) approach, based on a systematic examination of various written sources focusing on global shipbuilding policies and theoretical frameworks. Furthermore, supportive policies are required to promote decarbonization and compliance with IMO standards (such as the Hong Kong Convention) in order to ensure that the industry remains safe, environmentally sustainable, and competitive in the global market.